A carboxylic azo monomer and its homopolymer: synthesis, self-organization and fluorescence behaviour in solution. Issue 2 (26th September 2014) - Ren, Hao; Chen, Dong; Shi, Yan; Yu, Haifeng; Fu, Zhifeng
Abstract : The fluorescence of a carboxylic azo monomer and its homopolymer was studied in solution, which can be controlled by solvent polarity, pH value and photoirradiation. Abstract : We report special self-organization and fluorescence emission behaviours of a carboxylic azo monomer, 6-[4-(4-carboxylphenylazo)phenoxyl]hexyl methacrylate (M6AzCOOH), and its homopolymer (PM6AzCOOH) in solution. The monomer M6AzCOOH and its homopolymer PM6AzCOOH were non-fluorescent in N, N -dimethyl formamide (DMF) solution but became fluorescent, induced by the addition of water. The intensity of fluorescence emission increased with the amount of water in the mixed solvent and was sensitive to the pH value of the solution. The transmission electron microscopy (TEM) image reflected that vesicle-like structures formed due to the self-organization of PM6AzCOOH in water–DMF mixed solvent, and these structures changed into other forms of aggregation when the pH value of the solution was modified. The photoresponsive behaviour of the homopolymer in solution was investigated upon UV irradiation, demonstrating that trans – cis isomerization of azobenzene was hindered by the formation of aggregation and the change of aggregation form was responsible for the fluorescence emission behaviours.